2015
DOI: 10.1093/brain/awv355
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β dimers in the absence of plaque pathology impair learning and synaptic plasticity

Abstract: Despite amyloid plaques, consisting of insoluble, aggregated amyloid-β peptides, being a defining feature of Alzheimer's disease, their significance has been challenged due to controversial findings regarding the correlation of cognitive impairment in Alzheimer's disease with plaque load. The amyloid cascade hypothesis defines soluble amyloid-β oligomers, consisting of multiple amyloid-β monomers, as precursors of insoluble amyloid-β plaques. Dissecting the biological effects of single amyloid-β oligomers, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 80 publications
6
76
0
Order By: Relevance
“…Although plaques and tangles have traditionally been regarded as the main histopathological hallmarks of AD, a large body of evidence accumulated over the past decade suggests that soluble forms of these proteins are sufficient to trigger the development of the neurotoxicity process in AD (Berger et al., 2007; Bittner et al., 2010; Chabrier, Cheng, Castello, Green & LaFerla, 2014; Forner et al., 2017; Guerrero‐Munoz, Gerson & Castillo‐Carranza, 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu, Okamoto, Lipton & Xu, 2014). These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although plaques and tangles have traditionally been regarded as the main histopathological hallmarks of AD, a large body of evidence accumulated over the past decade suggests that soluble forms of these proteins are sufficient to trigger the development of the neurotoxicity process in AD (Berger et al., 2007; Bittner et al., 2010; Chabrier, Cheng, Castello, Green & LaFerla, 2014; Forner et al., 2017; Guerrero‐Munoz, Gerson & Castillo‐Carranza, 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu, Okamoto, Lipton & Xu, 2014). These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014). In addition, we have also demonstrated that Aβ oligomers modulate the development of tau pathology and accelerate cognitive and synaptic impairments (Chabrier et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative measurements underpinned the absence of considerable amounts of insoluble Aβ (Fig. 4) and revealed Aβ-levels that are in the same range as those in wild-type mice [29] and below those of wild-type naked mole rats [34]. …”
Section: Discussionmentioning
confidence: 99%
“…The brain was immediately snap-frozen in liquid nitrogen and stored at −80 °C. Fractionation of brain tissue was performed by preparative ultracentrifugation as described previously [29]. In brief, brain tissue was homogenated in 9 volumes of TBS buffer (150 mM sodium chloride, 50 mM Tris, pH 7, supplemented with protease inhibitor, Complete EDTA-free, Roche, Basel, Switzerland) and subsequently centrifuged (100,000 g, 4 °C, 1 h).…”
Section: Methodsmentioning
confidence: 99%
“…In AD brains, A␤ 40 and A␤ 42 are the predominant peptide isoforms, the latter of which is believed to aggregate faster and thusly considered more neurotoxic [3]. For example, recent evidence supports soluble A␤ 42 dimers as the neurotoxic isoform precipitating AD pathology [4][5][6].…”
Section: Introductionmentioning
confidence: 99%